2020
DOI: 10.1021/jacs.9b13106
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Catalysis Improves the Properties of CO2-Derived Polymers: Poly(cyclohexene carbonate-b-ε-decalactone-b-cyclohexene carbonate) Adhesives, Elastomers, and Toughened Plastics

Abstract: Carbon dioxide/epoxide copolymerization is an efficient way to add value to waste CO2 and to reduce pollution in polymer manufacturing. Using this process to make low molar mass polycarbonate polyols is a commercially relevant route to new thermosets and polyurethanes. In contrast, high molar mass polycarbonates, produced from CO2, generally under-deliver in terms of properties, and one of the most widely investigated, poly­(cyclohexene carbonate), is limited by its low elongation at break and high brittleness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
196
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(197 citation statements)
references
References 82 publications
(159 reference statements)
1
196
0
Order By: Relevance
“…The peel strength (2.8–8.0 N cm −1 ) and loop tack (4.1–8.2 N cm −1 ) of the prepared PSAs indicated that the PSAs could be used as general acrylic PSAs and optically clear adhesives [ 8 , 47 , 48 , 49 ]. In particular, the PSA obtained using a DBM concentration of 0.1 mol% and a 4DP-IPN loading of 10 ppm presented both excellent creep resistance (holding time > 100 h) and transparency (98.5%), which rendered it the most suitable PSA as an optically clear adhesive for electronics.…”
Section: Resultsmentioning
confidence: 99%
“…The peel strength (2.8–8.0 N cm −1 ) and loop tack (4.1–8.2 N cm −1 ) of the prepared PSAs indicated that the PSAs could be used as general acrylic PSAs and optically clear adhesives [ 8 , 47 , 48 , 49 ]. In particular, the PSA obtained using a DBM concentration of 0.1 mol% and a 4DP-IPN loading of 10 ppm presented both excellent creep resistance (holding time > 100 h) and transparency (98.5%), which rendered it the most suitable PSA as an optically clear adhesive for electronics.…”
Section: Resultsmentioning
confidence: 99%
“…Additional efforts should be also directed to close the urgent gap in creating highly stereoselective and sequence-controllable ROP that allows for immediate access to functionalized PAHAs, as similar remarkable controls have been achieved in the ROP of lactones and other heterocyclic monomers. [108][109][110][111][112] One of the foreseeable challenges is the scale-up of monomer synthesis. Unlike monomers of LA and many anhydrides that have seen success under large-scale industrial production, 113 most of OCA monomers are subjected to repetitive recrystallization for potential industrial scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of T g values also potentially allows for the preparation of multiblock thermoplastic elastomers. [97][98][99]…”
Section: Methodsmentioning
confidence: 99%